Liquidity Management and Profitability: A Case Study of Listed Manufacturing Companies in Sri Lanka - Priya, K.; Nimalathasan, B. (My University, 2013)
Liquidity management and profitability are very important issues in the growth and survival of business and the ability to handle the trade-off between the two a source of concern for financial managers.The study is also aimed at finding the effect of changes in liquidity levels on profitability of manufacturing companies in Sri Lanka. The study covered listed manufacturing companies in Sri Lanka over a period of past 5 years from 2008 to 2012. Correlation and regression analysis were used in the analysis and findings suggest that there is a significant relationship exists between liquidity and profitability among the listed manufacturing companies in Sri Lanka. Suggested that Inventory Sales Period (ISP), Current Ratio (CR)and are significantly correlated with Return on Asset (ROA), Operating Cash Flow Ratio (OCFR)are significantly correlated with Return on Equity (ROE) 5 percent level of significance. At the same time ISP and OCFR also are significantly correlated with ROA, Creditors Payment Period (CPP) also is significantly correlated with ROE at 1 percent level of significance.
Keywords: Liqudity; Liquidity Management; Profitability.